High-Resolution Transperineal Ultrasound in Anorectal Malformations—Can We Replace the Distal Colostogram? - Palmisani, Francesca; Krois, Wilfried; Patsch, Janina; Metzelder, Martin; Reck-Burneo, Carlos A. (European Journal of Pediatric Surgery Reports, 2022)
Introduction Anorectal malformations (ARM) affect 1 in 5,000 newborns with a wide range of defects. In the absence of a visible fistula, the diagnosis and classification of ARM require an augmented pressure distal colostogram. This procedure can be done after a diverting colostomy has been performed and implies exposing the child to radiation. We hypothesized that high-resolution transperineal ultrasound could correctly diagnose the type of ARM, thus sparing radiation exposure.Case Description Four full-term male newborns with ARM and no visible anal opening were referred to our center for further management. A diverting descendostomy was performed in the first 48 hours of life in all cases. Prior to the reconstructive surgery, we performed a high-resolution transperineal ultrasound with 3D tomographic reconstruction of the perineal region to assess the urethra, the rectum, and a possible fistula. Findings were compared with a conventional augmented pressure distal colostogram. The image acquisition was fast and did not cause any additional distress to the children.Conclusion In all cases the results of the distal colostogram nicely correlated with the high-resolution transperineal ultrasound with 3D tomographic reconstruction. In the future, we envision a time when it can potentially replace the distal colostogram in preoperative assessment of ARM with no distress and exposure to radiation.
Keywords: anorectal malformations; ultrasound; diagnostics; reconstructive surgery